God As Mistery: Konsep Allah Transenden Dan Imanen Menurut Kallistos Ware - Dagi, Orna Nengsi (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2022)
This research is motivated by the data that the author collects from various sources and the author finds problems in understanding the existence of God both among theologians and non-theologians, where often the existence of a transcendent and immanent God is considered unreasonable, which is a contradiction if these two existences at the same time exist in the one and only God. There are different views, such as Pantheism, which holds that God is completely Transcendent and Deism, which holds that God is completely immanent. Therefore, the purpose of this article was written to provide readers with an understanding that the one God cannot be viewed only with one side, namely transcendent or immanent. But the one God is transcendent but at the same time He is also an immanent God. Therefore, the writer sees this from Kallistos Ware's point of view that there are two paradoxical truths of God, namely transcendent and immanent. So that this article becomes a frame for readers to understand the existence of one God, both transcendent and immanent.AbstrakPenelitian ini di latar belakangi oleh data yang digali penulis dari berbagai sumber dan penulis menemukan masalah dalam pemahaman tentang keberadaan Allah baik dalam kalangan para theolog maupun non-theolog, dimana seringkali keberadaan Allah transenden dan imanen dianggap tidak masuk akal, yang kontradiksi jika dua keberadaan ini sekaligus ada dalam diri Allah yang esa. Beberapa pandangan berbeda seperti Panteisme berpandangan Allah sepenuhnya Transenden dan Deisme berpadangan Allah sepenuhnya imanen. Oleh karena itu tujuan artikel ini ditulis untuk memberikan pemahaman kepada para pembaca bahwa Allah yang esa itu tidak dapat dipandang hanya dengan satu sisi saja yakni transenden atau imanen. Melainkan Allah yang esa itu transenden tetapi di saat yang sama Dia juga Allah yang imanen. Untuk itu penulis melihat hal ini dari sudut pandang Kallistos Ware bahwa ada dua kebenaran paradoks Allah yakni transenden dan imanen. Sehingga artikel ini menjadi bingkai bagi para pembaca dalam memahami keberadaan Allah yang esa baik transenden maupun imanen.